2014
DOI: 10.1080/09168451.2014.921564
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl trisulfide induces apoptosis in Jurkat cells by the modification of cysteine residues in thioredoxin

Abstract: We reported the regulation of protein function by oxidative modification of the specific cysteine residue(s) by diallyl trisulfide (DATS). In this study, we examined if DATS modifies the cysteine residue of thioredoxin (Trx) by urea-polyacryl amide gel electrophoresis. DATS modified two specific cysteine residues in Trx and this oxidative modification of cysteine residues would be sole causative of the apoptosis induced by DATS in leukemic cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…Ca 2+ can also activate endonuclease and degrade nuclear DNA. On the other hand, Ca 2+ overload within the cytoplasm may cause mitochondrial swelling, outer membrane rupture (Redza-Dutordoir and Averill-Bates 2016; Ha et al 2019), and even fragmentation under special conditions, which in turn can induce cellular apoptosis (Li et al 2015;Watanabe et al 2014). In the present study, intracellular ROS and cytoplasmic Ca 2+ in the PM 2.5 exposed cells significantly increased (Fig.…”
Section: Discussionsupporting
confidence: 46%
“…Ca 2+ can also activate endonuclease and degrade nuclear DNA. On the other hand, Ca 2+ overload within the cytoplasm may cause mitochondrial swelling, outer membrane rupture (Redza-Dutordoir and Averill-Bates 2016; Ha et al 2019), and even fragmentation under special conditions, which in turn can induce cellular apoptosis (Li et al 2015;Watanabe et al 2014). In the present study, intracellular ROS and cytoplasmic Ca 2+ in the PM 2.5 exposed cells significantly increased (Fig.…”
Section: Discussionsupporting
confidence: 46%
“…We previously showed that DATS inhibited cell cycle progression in cancer cells. [3,7,9] Marquez et al reported that cell proliferation regulates adipogenesis in human adipose tissue-derived mesenchymal stem cells. [43] Thus, the causal relationship between DATS-mediated cell cycle alteration and adipogenesis remains unclear, although DATS may influence adipogenesis through cell cycle regulation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…[2] We have previously reported on a range of positive health benefits of DATS, including hepato-protective, anticancer, and antithrombotic effects. [3][4][5][6][7][8][9] Obesity is a serious health problem; 39% of the world's adult population is overweight and 13% is obese. These proportions have been increasing year by year.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a lipophilic compound extracted from garlic, DATS has been shown to be a novel anticancer agent. Numerous studies have indicated that DATS has strong anti-proliferative and pro-apoptotic activities in many cell lines (51)(52)(53). DATS-rich garlic oil benefits blood anti-coagulation factors and further prevents the development of thrombus.…”
Section: Discussionmentioning
confidence: 99%